2005
DOI: 10.1074/jbc.m506928200
|View full text |Cite
|
Sign up to set email alerts
|

Fas-, Caspase 8-, and Caspase 3-dependent Signaling Regulates the Activity of the Aminophospholipid Translocase and Phosphatidylserine Externalization in Human Erythrocytes

Abstract: Apoptosis and erythrocyte senescence share the common feature of exposure of phosphatidylserine (PS) in the outer leaflet of the cells. Western analysis showed that mature red cells contain Fas, FasL, Fas-associated death domain (FADD), caspase 8, and caspase 3. Circulating, aged cells showed colocalization of Fas with the raft marker proteins G␣ s and CD59; the existence of Fas-associated FasL, FADD and caspase 8; and caspase 8 and caspase 3 activity. Aged red cells had significantly lower aminophospholipid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 65 publications
7
127
0
11
Order By: Relevance
“…This suggested that • OH-induced PS exposure was caspase-dependent in carp erythrocytes. This is in accordance with the report that oxidative stress induces death receptors (Fas) with subsequent caspase-8 and caspase-3 activation that triggers loss of aminophospholipid translocase activity with subsequent PS externalization in human erythrocytes [92,93]. The caspases-involved PS exposure may be closely associated with intracellular ROS and cytochrome c in fish erythrocyte.…”
Section: • Oh-induced Apoptosis In Fish Erythrocytessupporting
confidence: 91%
“…This suggested that • OH-induced PS exposure was caspase-dependent in carp erythrocytes. This is in accordance with the report that oxidative stress induces death receptors (Fas) with subsequent caspase-8 and caspase-3 activation that triggers loss of aminophospholipid translocase activity with subsequent PS externalization in human erythrocytes [92,93]. The caspases-involved PS exposure may be closely associated with intracellular ROS and cytochrome c in fish erythrocyte.…”
Section: • Oh-induced Apoptosis In Fish Erythrocytessupporting
confidence: 91%
“…in erythrocytes, a sort of apoptosis has been described that implicates caspase activity [60] and CD95/Fas-mediated triggering. Strikingly, translocation of CD95/Fas into rafts could trigger caspase activation in these cells too [61]. A series of works on raft function has also been carried out by investigating the effects of filipin, MβCD or cholesterol synthesis blockers, such as mevastatin, as raft disruptors and analyzed the resulting alterations of the apoptotic machinery.…”
Section: The Role Of Lipid Rafts In Apoptosismentioning
confidence: 99%
“…These reactive alkenals have been found to interfere with PtdSer asymmetry via redox dependent flippase (Castegna et al, 2004;Daleke, 2003;Tyurina et al, 2004b). Furthermore, much evidence indicates that oxidative modification of flippase by reactive alkenals and/or apoptotic proteins, resulting in asymmetric collapse (Castegna et al, 2004;Kagan et al, 2002;Mandal et al, 2005;Mohmmad Abdul and Butterfield, 2005;Tyurina et al, 2004a), is greatly elevated in the early apoptotic phenotype of AD models (Herrmann and Devaux, 1990;Kagan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Activated caspase-3 immunoreactivity has been detected in both neurons and astrocytes and found elevated in frontotemporal dementia (Su et al, 2000) and AD (Su et al, 2001). PtdSer exposure due to apoptosis has been found to occur downstream of caspase activation in some cell types (Mandal et al, 2002;Martin et al, 1996;Vanags et al, 1996); in non-neuronal cells like human erythrocytes, caspase activation is associated with loss of aminophospholipid translocase activity and subsequent PtdSer externalization (Mandal et al, 2005). Amnestic mild cognitive impairment (MCI) is considered a transition point between normal cognitive aging and dementia or probable AD (Petersen et al, 1999;Winblad et al, 2004).…”
Section: Introductionmentioning
confidence: 99%